Influence of the culture medium and pH on the growth of saprobic and ectomycorrhizal mushroom mycelia - Barros, Lillian (2008)
This paper reports the influence of culture medium and pH in the radial growth and growth rate of saprobic (Leucopaxillus giganteus) and ectomycorrhizal (Lactarius deliciosus and Suillus luteus) edible mushrooms mycelium. Leucopaxillus species are used in chemical industry for extraction of clitocybin antibiotic and Lactarius deliciosus and S. luteus are highly consumed and commercialized in Trás-os-Montes region (Northeast of Portugal). Methods. Two different solid culture media (Melin- Norkans, MMN and Potato Dextrose Agar, PDA) and two pH values (5 and 6) were tested in order to achieve the best conditions to mycelium growth. Results. The pH had no influence in its morphological characteristics, while the culture medium only affected S. luteus mycelium. For all the tested conditions, the growth rate of Leucopaxillus giganteus mycelium was significantly higher (P<0.05) than the growth rate of ectomycorrhizal mushrooms mycelium. Conclusion. The pH had a significantly influence in the growth of Leucopaxillus giganteus and S. luteus when PDA medium was used, and MMN proved to be a better culture medium for Lactarius deliciosus and S. luteus mycelia growth